ANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS HASIL TREATMENT SULAM ALIS TEKNIK OMBRE DI SALON BBC HAIR AND BEAUTY STUDIO - Tasya Vinanda Panestuti; Octaverina Kecvara Pritasari; Sri Dwiyanti; Novia Restu Windayani (Program Studi Pendidikan Tata Rias, 2025)
The purpose of this study was to determine customer satisfaction in terms of price perception, service quality, and facilities for ombre eyebrow embroidery treatment at BBC hair and beauty studio and the quality of the results of ombre eyebrow embroidery treatment at BBC hair and beauty studio. The type of quantitative descriptive research used by the author in this study. The method used to obtain data is by distributing questionnaires measured by a Likert scale. The Customer Satisfaction Index (CSI) method is used to process the results of the analysis. The average value of the customer satisfaction index for the price perception aspect is 0.81 with a very satisfied level of satisfaction, the average value of the customer satisfaction index for the service quality aspect is 0.82 with a very satisfied level of satisfaction, the average value of the customer satisfaction index for the facility aspect is 0.78 with a satisfied level of satisfaction. The highest aspect of customer satisfaction for ombre eyebrow embroidery treatment is the aspect of service satisfaction. The quality of the results obtained an average value of 0.85 with a very satisfied level of satisfaction, so the quality of the eyebrow embroidery treatment results is in accordance with customer expectations. Keywords: eyebrow embroidery, ombre technique eyebrow embroidery, price perception, service quality, facilities, quality of results.